Effectiveness of low dose of rapamycin in preventing seizure-induced anxiety-like behaviour, cognitive impairment, and defects in neurogenesis in developing rats. (2nd January 2020) - Liu, Furong; Wu, Meiling; Kai, Jiejing; Dong, Jingyin; Zhang, Binbin; Liu, Luna; Zhu, Feng; Zeng, Ling-Hui
Abstract: Aims: Previous studies have demonstrated that rapamycin prevents seizure-induced anxiety-like behaviors. However, rapamycin had been used at a higher dose of 3 mg/kg and resulted in side effects in immature animals. This work was designed to explore whether a lower dose of rapamycin has similar efficacy but has milder side effects. Methods: Acute seizures were induced by injection of pilocarpine at postnatal 10-day Sprague-Dawley rats. Western blot analysis was used to detect changes in mammalian target of rapamycin (mTOR) pathway after seizure. Immunofluorescent intensity of doublecortin (DCX) was conducted to evaluate the development of neurons in hippocampus. Morris water maze and Y-maze test were used to assess cognitive functions and open-field test and elevated plus maze were used to detect anxiety-like behaviors 4 weeks after seizure onset. Results: mTOR pathway was abnormally activated with two peaks after pilocarpine-induced seizures, and no difference of DCX-positive cells and body weight were noticed between control and pilocarpine-induced seizure rats. Pilocarpine-induced seizure in postnatal 10 days rats did not exert impairment on cognitive functions, but resulted in obvious anxiety-like behaviors. Low dose of rapamycin at 0.3 mg/kg significantly reversed seizure-induced increase of p-S6 levels as well as abnormal anxiety-like behaviors. In addition, rapamycin at the dose of 0.3mg/kg did not affect normal development and cognitive functions. Conclusion: lower doses of rapamycin should be used in infants compared with older children or adults.